Clinical efficacy of erlotinib, a salvage treatment for non-small cell lung cancer patients following gefitinib failure - Cho, Kyoung Min (Korean J Intern Med, 2015)
BACKGROUND/AIMS: The purpose of this study was to identify predictive factors for erlotinib treatment in non-small cell lung cancer (NSCLC) patients following gefitinib failure. METHODS: Forty-five patients with NSCLC who were treated with erlotinib following gefitinib failure at Seoul National University Hospital between August 2005 and November 2011 were enrolled. Epidermal growth factor receptor (EGFR) mutation status, pathologic findings and other clinical factors, including response to tyrosine kinase inhibitors (TKIs) and progression-free survival (PFS), were evaluated. RESULTS: Of the 45 patients, 40 patients (88.8%) had adenocarcinoma. The following EGFR mutations were observed: five patients with a deletion of exon 19, six patients with an L858R mutation, three patients with wild-type EGFR, and 31 patients with unknown mutations. The response rate of erlotinib was 4.4%, and stable disease was 42.2%. The median PFS for erlotinib was 2.6 months (95% confidence interval, 1.4 to 3.7). Patients with a PFS ≥ 4 months during previous gefitinib treatment had a significantly longer PFS with erlotinib (3.3 months vs. 1.6 months, respectively; p < 0.01) than patients with PFS < 4 months with gefitinib. According to multivariate analyses, PFS ≥ 4 months for previous gefitinib treatment was significantly associated with prolonged PFS with erlotinib (p = 0.04). However, the response rate of gefitinib and treatment sequence were not associated with prolonged PFS with erlotinib (p = 0.28 and p = 0.67, respectively). CONCLUSIONS: Following rechallenge with the EGFR TKI erlotinib following gefitinib failure, patients who showed prolonged PFS with gefitinib benefit from erlotinib. However, further prospective studies are needed to confirm these findings.